Developing therapeutic computer programs with particular reference to a program to teach coping strategies to problem drinkers. - Yates F (Journal of Mental Health)
A computer-assisted relapse management program (CARM) was developed as a therapeutic tool to guide problem drinkers through a problem-solving procedure and provide access to a database of coping strategies. The program was tested with eleven randomly selected hospital inpatients and compared with conventional problem-solving sessions undertaken without the computer. Feedback collected immediately after the sessions and an inspection of the action plans generated indicated that problem-solving with the computer and therapist support was preferred and more likely to stimulate original coping ideas than a therapist-only problem-solving session. Ways of improving the therapeutic quality of computer interactions based on later work using principles taken from clinical psychology are described.